Matrix of interprofessional competencies in multiprofessional health residencies: construction of a proposal - Sâmara Fontes Fernandes; Rodrigo Jácob Moreira de Freitas; Isadora Lorenna Alves Nogueira; Lucas Souza Leite; Rafael Jeremias de Aquino Nunes; Maria Rocineide Ferreira da Silva (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To construct a matrix of interprofessional competencies produced in Multiprofessional Health Residencies in the interior of Rio Grande do Norte. Method: Qualitative study, with a deductive method for theorization and construction of the competency matrix. It was organized into three phases: theoretical, field and analytical phase. Developed in multi-professional residencies in the interior of northeastern Brazil, with a sample of 41 subjects: 30 students, 06 preceptors, 04 professors and 01 municipal health manager. Focus group and interview data collection techniques were used, carried out from November 2022 to August 2023. Deductive thematic analysis was applied. All ethical principles were respected. Results: The matrix was organized on three levels of competencies: common, professional-guiding, and collaborative. It is demonstrated using a table that organizes the type of competency, the interviewees’ speeches and the competencies identified in the study, guided by international literature. Conclusion: It was possible to construct the interprofessional competencies matrix. The matrix foresees a contemporary professional profile, demonstrating the need for improvements to professional reorientation from an interprofessional perspective to meet the demands of this new professional profile.